367 SUSCEPTIBILITY WEIGHTED IMAGING: VALIDATION OF AN INNOVATIVE MAGNETIC RESONANCE IMAGING TECHNIQUE FOR MEASURING BRAIN IRON. (1st January 2006) - Fox, J.; Mueller, C.; Magaki, S.; Obenaus, A.; Haacke, E. M.; Kirsch, W. M.
Abstract : Although iron perturbations have long been connected to Alzheimer's disease (AD) (Connor et al, 1992; Robinson et al, 1995) their possible role is still very much unclear. To assess whether disruption of iron metabolism is indeed one of the primary events leading to AD or is just a bystander, new techniques are necessary that can sensitively measure levels of steady-state brain iron in patients. One such technique is susceptibility weighted imaging (SWI) where local phase differences are used to map brain iron. Phase and T2 prime do not suffer from reversibility effects that nullify iron signals and are thus superior to standard T2 sequences. The advantages of SWI over conventional MR sequences for iron detection have been described (Haacke et al, 2004; Haacke et al, 2005). To further validate this technique a mouse brain dissection protocol has been developed that enables us to dissect 24 distinct regions of the mouse brain. Furthermore, iron extraction methods from Nelson et al (2000) have been adapted to allow extraction of loosely bound iron (iron bound to phosphate esters, carbohydrates, and organic acids), non-heme bound iron (iron not bound to heme and heme-like structures), and total iron from these brain regions. Iron content was then measured using graphite furnace atomic absorption spectroscopy (GFAAS). Variation in the iron content between brain regions has been found. To preserve most of the loosely bound iron pool microwave irradiation has been used to euthanize animals. IRP-2 knockout mice, which have been shown to accumulate higher iron levels in the brain (LaVaute et al, 2001), are being compared to age matched wild-type mice in this study. IRP-2 regulates intracellular iron metabolism by binding to iron response elements (IRE) located at the 5′ or 3′ UTR of mRNA of proteins responsible for the intake and storage of iron in the cell and thereby stabilizing the respective mRNA or blocking its translation. Results have shown that the methodology and use of the IRP-2 knockout mouse model are valid ways to quantitate brain iron content in vivo.